Nanomedicine Strategies Utilizing Lipid-Based Nanoparticles for Liver Cancer Therapy: Exploring Signaling Pathways and Therapeutic Modalities - Fereshteh Asgharzadeh; Maryam Moradi Binabaj; Sahar Fanoudi; William C. Cho; Yu-jeong Yang; Maryam Azarian; Mehdi Shafiee Ardestani; Nasim Nasiri; Marzieh Ramezani Farani; Yun Suk Huh (Advanced Pharmaceutical Bulletin)
Liver cancer, specifically hepatocellular carcinoma (HCC), is the second leading cause of cancer-related deaths, following pancreatic cancer. The 5-year overall survival rate for HCC remains relatively low. Currently, there are multiple treatment options available for HCC, including systemic drugs, minimally invasive local therapies such as radiofrequency ablation, transarterial chemoembolization (TACE), and arterial radioembolization (TARE), as well as surgical interventions like liver resection or transplantation. However, the effectiveness of drug delivery to the cancerous liver is hindered by pathophysiological changes in the organ. In order to address this challenge, lipid-based nanoparticles (LNPs) have emerged as promising platforms for delivering a diverse range of therapeutic drugs. LNPs offer various structural configurations that enhance their physical stability and enable them to accommodate different types of cargo with varying mechanical properties and degrees of hydrophobicity. In this article, we provide a comprehensive review of the current applications of LNPs in the development of anti-HCC therapies. By examining the existing research, we aim to shed light on the potential future directions and advancements in this field.